MODERN METHODS OF ESTIMATION CAPITAL VALUE - Khudoykulov Khurshid Khurramovich (Journal of Artificial Intelligence and Digital Economy, 2024)
The article indicates the scientific and theoretical aspects of using the method of multiplier coefficients in estimating capital value, focusing on using the EV / S and EV / EBITDA methods of evaluating capital value used in emerging market countries. In particular, based on data from Qizilqumsement, Kokand Mechanical Plant, Kvars, Uzmetkombinat from 2015 to 2019, the company's capital value is estimated. In addition, the existing problems in using EV / S and EV / EBITDA methods estimate and identify the value of capital of the joint-stock company. Then, scientific proposals and practical recommendations were developed by the author